ENCOURAGING VIRTUAL REALITY EXPERIENCES: THE EFFECT ON TOURISTS’ INTENTION TO VISIT TOURISM DESTINATION - Cheng-Wen LEE; Idris IDRIS (Geo Journal of Tourism and Geosites)
This study aims to analyze the relationship among virtual reality experiences, virtual reality experiential outcomes, destination awareness, and intention to visit a destination. It is also investigated rega rding the mediating role of the virtual reality experiences and destination awareness on intention to visit. This study used a questionnaire to collect data from tou rist experiences using a virtual reality application. The 115 data collected were analysed by Partial Least Square (PLS) analysis. The finding indicates that the virtual reality experience does not significantly influence intention to visit. Furthermore, t he results of the virtual reality experience also proved not to significantly influence intention to visit, so the virtual reality experiential outcomes were not able to become an important factor as an indirect relationship between virtual reality experiences and intention to visit a destination. However, the virtual reality experience still has an influence on destination awareness and has an indirect effect on intention to visit destinations through mediation from destination awareness. Therefore, tourism managers must be able to utilize VR as an information medium related to the destinations offered, so that tourists will get a lot of useful information to be more familiar with these destinations which will ultimately influence the intention to visit a destination. The limitations of the study and future research agenda are also highlighted.